2015
DOI: 10.1682/jrrd.2014.10.0239
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physical therapy delivery via home video telerehabilitation on functional and health-related quality of life outcomes

Abstract: Abstract-This

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
119
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(129 citation statements)
references
References 27 publications
8
119
0
1
Order By: Relevance
“…Participant 6 DISCUSSION Clients in this study reported both benefits and barriers to telehealth, with overall benefits outweighing barriers. This replicates previous research findings of an overall positive client experience in which reported benefits outweighed barriers (Chou et al, 2013;Eikelboom & Atlas, 2005;Levy et al, 2015;Polinski et al, 2015;Waibel et al, 2017;Young et al, 2011). However, even when clients report an overall benefit from telehealth service delivery, their opinions and preference for telehealth may not be entirely positive (Sorenson, 2008).…”
Section: Close-ended Responsessupporting
confidence: 84%
See 3 more Smart Citations
“…Participant 6 DISCUSSION Clients in this study reported both benefits and barriers to telehealth, with overall benefits outweighing barriers. This replicates previous research findings of an overall positive client experience in which reported benefits outweighed barriers (Chou et al, 2013;Eikelboom & Atlas, 2005;Levy et al, 2015;Polinski et al, 2015;Waibel et al, 2017;Young et al, 2011). However, even when clients report an overall benefit from telehealth service delivery, their opinions and preference for telehealth may not be entirely positive (Sorenson, 2008).…”
Section: Close-ended Responsessupporting
confidence: 84%
“…Saved time and reduced need for transportation are commonly reported benefits of telehealth (Eikelboom & Atlas, 2005;Kairy et al, 2013;Kruse et al, 2017;Levy et al, 2015;Polinski et al, 2015) that were confirmed in this study. It may be a benefit to match clients to telehealth and in-person delivered services based on needs such as time and transportation barriers, and need for hands on or manual components of treatment, including consideration of support of a caregiver, friend, or family member at home.…”
Section: Close-ended Responsessupporting
confidence: 83%
See 2 more Smart Citations
“…[27] Telehealth and remote videoconferencing have been effectively used to deliver rehabilitation after total knee replacement, [28] stroke, [29] and physical therapy to Veterans. [30] Based on the information collected from residents of the Humanities Foundation, a telehealth delivered physical activity program was implemented within two of the Humanities properties utilizing the Otago exercise program, a physical therapy program endorsed by the Centers for Disease Control to improve balance and strengthening in community dwelling older adults [8] and by the National Council on Aging as the highest level of evidence for fall prevention programs. [31] Participants were also given wearable activity monitors, Fitbits, to help track their activity.…”
Section: Introductionmentioning
confidence: 99%